Implementasi Lean Inventory Management dalam Mengurangi Biaya Persediaan di Perusahaan Manufaktur - Firdausi Amaliyah; Taufik Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Lean Inventory Management is a systematic approach that focuses on reducing waste in the inventory management process to improve operational efficiency and reduce costs. This study aims to analyze the impact of Lean Inventory Management implementation on reducing inventory costs in manufacturing companies. This research uses a case study method in a manufacturing company that has implemented Lean Inventory Management. Data were collected through in-depth interviews, direct observation, and analysis of company documents. The analysis techniques used include descriptive and comparative analysis to measure changes in inventory costs before and after implementation. The results showed that the implementation of Lean Inventory Management succeeded in significantly reducing inventory costs. Some of the strategies implemented include the implementation of Just-In-Time (JIT), reduction of buffer inventory levels, improved coordination with suppliers, and the use of information technology for real-time inventory monitoring. In addition, the company also noted improved operational efficiency and customer satisfaction as a positive impact of implementing Lean Inventory Management. This study concludes that Lean Inventory Management is an effective approach to reduce inventory costs in manufacturing companies. Proper implementation of lean strategies can result in significant cost savings